MORPHOLOGICAL ANALYSIS OF AGE DYNAMICS OF BIOMECHANICAL PROPERTIES OF KNEE LIGAMENTS OF THE KNEE JOINT IN HUMAN FETUSES - A. E. Strizhkov (Сеченовский вестник, 2017)
A study of the structure and biomechanical properties of knee joint ligaments in 200 fetus corpses at the age of 12 to 38 weeks of intrauterine development was conducted. A correlation was established between age dynamics of elastic-strength properties and complexity of ﬁbroarchitectonics of ligaments. The strength limit of the ligament substance decreases with the formation of bundles of collagen ﬁbers of the second and third orders and increases with their maturation. The modulus of elasticity directly depends on the degree of tortuosity and longitudinal curvature of bundles of collagen ﬁbers of the ﬁrst and second orders. The limiting relative elongation is greatest with relative prevalence of endotenonium over bundles of collagen ﬁbers of the ligaments